Análisis de las Universidades para el Bienestar Benito Juárez García: retos y limitaciones a seis años de su implementación - Ramírez Sánchez, Rubén Darío (2025)
We offer a critical review on the process through which Benito Juárez García Welfare Universities were founded starting in 2019 during Andrés Manuel López Obrador period (2018-2024). The objective of the work consists of analyzing the basic foundations that served as the basis for their institutionalization. In order to carry out the exercise, a qualitative strategy was used, through the analysis of official documents and newspaper studies, whose inputs allowed us to reflect on the emergence and complexity of the expansion and development of this institution; We found strong deficiencies in the model that promised to massify the right to education and instead retained an educational model very similar to the previous ones, which maintains a centralist structure, poor working conditions and many structural limitations, which have aroused from student and teacher protests, to criticism from education specialists and public opinion on the lack of compliance with its main objectives.